E-LKPD with PMRI Approach Using Liveworksheet on Cube and Block Materials - Afrianti, Lusiana (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
This study aims to produce teaching materials in the form of E-LKPD based on PMRI approach on Cube and block material that is valid, practical, and has a potential effect on the ability to understand mathematical concepts of students in Class VIII of SMP Negeri 18 OKU. The research method used is a research development method consisting of preliminary stage (analysis stage and design stage) and prototyping stage using formative evaluation flow (self-evaluation, expert review, one-to-one, small group, and field test). Data collection was conducted using questionnaires, interviews and tests. The results of this study are: (1) E-LKPD based on PMRI approach developed qualitatively valid seen from the comments and suggestions of the validator, in addition quantitatively with the results of the validation sheet analysis by obtaining an average score of 80.9 at the expert review stage. These results show that the PMRI approach based on E-LKPD is in the very good category (2) e-LKPD based on PMRI approach developed is very practical qualitatively and quantitatively by obtaining an average score of 84 at the one-to-one stage, 88 at the small group stage and 88 at the field test stage. (3) E-LKPD based on PMRI approach developed has a potential effect on the ability to understand mathematical concepts with an average value of 73.8.